BAND-PASS FILTER CIRCUIT DESIGN FOR MULTI-FREQUENCY ELECTRICAL IMPEDANCE TOMOGRAPHY SYSTEM - Ayu Jati Puspitasari; Endarko Endarko (BATAN, 2019)
BAND-PASS FILTER CIRCUIT DESIGN FOR MULTI-FREQUENCY ELECTRICAL IMPEDACE TOMOGRAPHY SYSTEM. Electrical Impedance Tomography (EIT) is one of the emerging imaging technologies recently. The principle of EIT system is inject electric current into impedance object and measure the voltage based on the electrodes array. The current source that precise, stable, and wide-bandwidth is required to obtain voltage measurements accurately. The current source used for this EIT system is Voltage-Controlled Current Source (VCCS). The VCCS block circuit consists of several circuits, one of them is a filter circuit. The suitable filter for multi-frequency EIT system is band-pass filter. This research has been designed and fabricated a band-pass filter with cut-off frequency 1 and 250 kHz, which is using Butterworth coefficient, unity gain, and Sallen-Key topology.